Characteristics and accurate identification of Pantoea dispersa with a case of spontaneous rupture of hepatocellular carcinoma in China: A case report. Issue 2 (14th January 2022) - Yang, Yang; Hu, Haitao; Zhou, Chenglin; Zhang, Wenyun; Yu, Yang; Liu, Qingyi; Lu, Taohong; Zhang, Qingfang
Abstract : Supplemental Digital Content is available in the text Abstract: Introduction: Pantoea dispersa belongs to the genus Pantoea, which is isolated from Enterobacteriaceae . It has been reported to cause some kinds of infections, but there are few detailed studies on it, especially its characteristics and identification methods, which has caused a lot of trouble in clinical work. Patient concerns: A 51-year-old Chinese man was admitted to our hospital with a 7-hour history of progressive abdominal pain. He was previously diagnosed with liver cirrhosis secondary to chronic hepatitis B infection and hepatocellular carcinoma. An emergency hepatic artery embolization for hemostasis was performed under local anesthesia. Forty-eight hours later, the patient presented sudden onset of high fever up to 39.0 °C and chill. Diagnosis: Morphological and phenotypic profiles were performed for preliminary identification for P dispersa . The biochemical features were obtained by VITEK 2 Test Kit. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry analysis and 16S ribosomal RNA sequencing were performed to accurately identify P dispersa . Intervention: Antibiotic therapy of intravenous ceftazidime was started empirically. The antibiotic treatment was switched to intravenous cefepime at the same time because of suspected ceftazidime treatment failure and microbiological sensitivity. Outcomes: The patient remained afebrile, and the second blood culture results were negative. Chest X-ray was normal as well. In order to control the progression of the hepatic lesion, transarterial chemoembolization was performed under local anesthesia. After completion of 14 days of antibiotic treatment, the patient was discharged with no signs of recurrence. Conclusion: P dispersa, a gram-negative bacterium rod, were facultative anaerobic, which displayed yellow pigmentation, round, raised, smooth on culture plates. Conventional analysis was difficult to complete its identification. With biochemical tests, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry analysis and 16S ribosomal RNA sequencing, P dispersa can be accurately identified. It will help physicians understand the related clinical manifestations and make timely and effective treatment for patients.